2022
DOI: 10.1186/s40164-022-00313-x
|View full text |Cite
|
Sign up to set email alerts
|

A pan-cancer analysis of the oncogenic role of leucine zipper protein 2 in human cancer

Abstract: In this study, we aimed to perform a pan-cancer analysis of leucine zipper protein 2 (LUZP2). A standardized TCGA pan-cancer dataset was downloaded. Differential expression, clinical prognosis, genetic mutations, immune infiltration, epigenetic modifications, tumor stemness and heterogeneity were analyzed. We conducted all analyses through software R 3.6.3 and its suitable packages. Compared to normal samples, we observed that the LUZP2 mRNA expression was significantly upregulated in LGG, PRAD, LUSC and downr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…LUZP2 , a leucine zipper protein, is associated with Alzheimer’s Disease and schizophrenia, as well as cognitive performance in the normal elderly population 43 . It is differentially expressed in several cancers, including low grade gliomas 44 . Similarly, RERGL is differentially expressed in schizophrenia 45 , while its expression is significantly higher in meningiomas compared to healthy tissue 46 .…”
Section: Resultsmentioning
confidence: 99%
“…LUZP2 , a leucine zipper protein, is associated with Alzheimer’s Disease and schizophrenia, as well as cognitive performance in the normal elderly population 43 . It is differentially expressed in several cancers, including low grade gliomas 44 . Similarly, RERGL is differentially expressed in schizophrenia 45 , while its expression is significantly higher in meningiomas compared to healthy tissue 46 .…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to normal samples, we found that the LUZP2 mRNA expression was significantly higher in PRAD. In terms of overall survival, low expression of LUZP2 was significantly associated with poor prognosis in PRAD [29]. However, the effect of LUZP2 on PD has not been reported, which may be a new marker for PD treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For tumor heterogeneity, we compared homologous recombination deficiency (HRD), loss of heterozygosity (LOH), neoantigen (NEO), tumor ploidy, tumor purity, mutant-allele tumor heterogeneity (MATH), tumor mutation burden (TMB) and microsatellite instability (MSI) [ 43 , 44 ] between two subtypes. All these data could be obtained from our previous study [ 9 ]. In addition, for the TIME analysis, we used Cibersortx and ESTIMATE algorithms [ 45 47 ] to assess the overall tumor microenvironment and immune components and compared the differences of tumor microenvironment scores and 54 immune checkpoints between these two subtype.…”
Section: Methodsmentioning
confidence: 99%